Reliability and Validity of the HIV Disability Questionnaire (HDQ) with Adults Living with HIV in the United States. (25th November 2019) - O'Brien, Kelly Kathleen; Kietrys, David; Galantino, Mary Lou; Parrott, James Scott; Davis, Tracy; Tran, Quang; Aubry, Rachel; Solomon, Patricia
Objectives: To assess measurement properties of the HIV Disability Questionnaire (HDQ) among adults with HIV in the United States. Methods: We administered the HDQ, World Health Organization Disability Assessment Schedule II (WHODAS 2.0), and a demographic questionnaire. For internal consistency reliability, we calculated Cronbach α and Kuder-Richardson-20 (KR-20) statistics for disability and episodic scores, respectively (≥0.80 acceptable). For test–retest reliability, we calculated intraclass correlation coefficients (>0.8 acceptable). For construct validity, we tested 15 a priori hypotheses assessing correlations between HDQ and WHODAS 2.0 scores. Results: Of the 128 participants, the majority were males (68%), median age 51 years, taking antiretroviral therapy (96%). Cronbach α ranged from 0.88 (social inclusion) to 0.93 (uncertainty). The KR-20 ranged from 0.86 (cognitive) to 0.96 (uncertainty). Intraclass correlation coefficients ranged from 0.88 (physical, cognitive, social inclusion) to 0.92 (mental–emotional). Of the 15 hypotheses, 13 (87%) were confirmed. Conclusions: The HDQ demonstrates internal consistency reliability, test–retest reliability, and construct validity when administered to a sample of adults with HIV in the United States.